Thermally exfoliated fluorinated graphite for NO2 gas sensing. Issue 12 (22nd September 2016) - Sysoev, V. I.; Bulusheva, L. G.; Asanov, I. P.; Shubin, Yu. V.; Okotrub, A. V.
Abstract : Few‐layer graphene samples have been obtained by a thermal expansion of bromine‐intercalated fluorinated graphite with a ∼C2 F matrix composition at 600, 700, and 800 °C. X‐ray photoelectron spectroscopy detected that the products contained almost the same quantities of foreign atoms independently on the exfoliation temperature. However, the Raman spectra showed a progressive increase in the relative intensity of the D mode with the temperature growth. This was attributed to more edge states developed in graphene planes at the higher temperature. Thin films from obtained samples were tested as sensors using 1000 ppm nitrogen dioxide (NO2 ) in argon. The film from few‐layer graphene produced at 800 °C had the largest relative response, while its recovery was quite low at room temperature. The sensor performances were related with the structural characteristics of the exfoliated graphenes. Left: Relative response of gas sensors based on few‐layer graphene products of an expansion of fluorinated graphite at 600, 700, and 800 °C toward 1000 ppm NO2 . Right: Proposed structures of the products.